2010
DOI: 10.1111/j.1551-2916.2010.04000.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymer‐Derived SiOC–barium–strontium aluminosilicate Coatings as an Environmental Barrier for C/SiC Composites

Abstract: Polysiloxanes polymer coatings were formed on carbon fiber‐reinforced silicon carbide (C/SiC) composites at 100°C in air with barium–strontium aluminosilicate (BSAS) as fillers. After the polymeric coatings were pyrolyzed at 1350°C under argon, a dense SiOC–BSAS‐coated C/SiC composite was obtained. The oxidation test in dry air and the corrosion test in water vapor were carried out on the coated composites at 1250°C, respectively. The results indicated that the polymer‐derived SiOC–BSAS coatings could protect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 27 publications
(41 reference statements)
0
16
0
Order By: Relevance
“…(b)]. It is believed that the formation of these pores is due to the pyrolysis of the polysilazane during the fabrication process . Figure (c) shows the XRD patterns of the BSAS coating.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(b)]. It is believed that the formation of these pores is due to the pyrolysis of the polysilazane during the fabrication process . Figure (c) shows the XRD patterns of the BSAS coating.…”
Section: Resultsmentioning
confidence: 99%
“…7,8 In the past decades, several EBCs systems have been developed, including yttria-stabilized zirconium, 7,9 barium strontium aluminosilicate (BSAS), 7,10-14 and rare-earth silicates. [15][16][17][18][19] Previously, most research has focused on the EBCs themselves only: studying their water vapor resistance, [9][10][11][12][15][16][17] fabrication process, 14,18,19 and hot corrosion behavior. 13,20,21 Very few works considered the failure behaviors of the entire system contained both the substrate and the EBCs.…”
Section: Introductionmentioning
confidence: 99%
“…The thickness of the SiO 2 scale is about 500 nm, which is much thinner than that of our previous study. 22 It is indicated that the yttrium silicate coatings are pretty dense. For the composites without yttrium silicate coatings, the carbon fibers are almost burnt out, leaving a lot of holes inside (Fig.…”
Section: Water-vapor Corrosion Behavior Of the Yttrium Silicates Coatmentioning
confidence: 99%
“…19 Compared with other technologies, polymer-derived ceramic coating process is a potential method due to its relative low cost, ability to coat complex structures, and low process temperatures. [20][21][22] With adding the active or inert fillers in the polymer precursors, the shrinkage during pyrolysis and resultant cracks of the coatings can be avoided. 23 In our previous study, 24 dense SiOC-BSAS was coated on C/SiC composites using polysiloxanes as polymer precursors and BSAS as inert fillers.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a new route to synthesize yttrium silicate from the pyrolysis of Y 2 O 3 powder filled silicone resin has been reported [14,15]. This route is a promising method because of good adhesive and covering ability of silicone resin, low process temperature, and relatively low cost [16,17]. Dense Y 2 Si 2 O 7 coating was fabricated on SiC foam by pyrolysis in air of silicone resin containing Y 2 O 3 powders [14], but the oxidation protection for C/SiC composites was not investigated.…”
Section: Introductionmentioning
confidence: 99%